Comparison Of Quarry Resource Estimation Using Cross Section And Contour Methods At PT. X, East Java, Indonesia - Devananda; Avellyn Shinthya Sari; Yazid Fanani; Nazario Gomez (Journal of Innovative and Creativity, 2025)
PT  X, located in Pasuruan, East Java, has been exploring for sirtu (sand and gravel) in a Mining Business License (IUP) area of 12.12 hectares. This study aims to estimate the quality and quantity of sirtu using two methods, namely Cross Section and Contour. The estimation results show that the volume of top soil obtained through the Cross Section method is 428,253 m³, while the Contour method produces a slightly lower volume of 417,964 m³. For the sludge volume, the Cross Section method estimated a volume of 7,404,289 m³, while the Contour method gave a higher estimate of 7,579,433 m³. The difference in estimation results between the two methods is due to the distance between the incisions used in the measurements as well as differences in the methodological approach. The total difference in volume obtained from the two methods amounted to 175,144 m³. This study provides important insights into the potential sludge resources in the ASA IUP area and shows how different methods can affect the estimation results. With this information, it is hoped that the company can make better decisions in the management and utilization of existing sludge resources. This research also emphasizes the importance of choosing the right method in natural resource exploration to obtain accurate and reliable estimates.